Analisis Kinerja Lalu Lintas Dan Solusi Simpang Tak Bersinyal Perempatan Duren Tangerang Selatan Dengan Metode PKJI 2014 - Adita Utami; Muhammad Abyan Daffa (Universitas Dr. Soetomo, 2024)
This research reviews the performance analysis of unsignalized intersection traffic at Duren Intersection. This research also discusses scenarios for repairing unsignalized intersections and forecasting traffic performance for the next five years. The purpose of this research is to determine the amaount of the intersection capacity at the Perempatan Duren, knowing the total volume of vehicles during peak hour conditions at the Perempatan Duren, knowing the performance of unsignalized intersection traffic at the Perempatan Duren, planning solutions to improve traffic performance at the Perempatan Duren, nd predicting the intersection performance in the next 5 years. The method used in this research is the Indonesian Highway Capacity Guideline method (PKJI) 2014. The results of this study indicate that the intersection capacity is 3216,72 skr/hour. Total vehicle volume during peak hour conditions was 2829 skr/hour. From the calculation results, the degree of saturation is 0.88 and the delay value is 15.14 seconds/skr. The level of service at the Perempatan Duren is C, where the traffic flow is stable and vehicle movements are affected by traffic volume. The chance of queuing at the Perempatan Duren ranges from 61.29% - 31.05%. Among the planned solutions, alternative 4 is widening the major and minor roads and alternative 5 is reducing side barriers by widening the major and minor roads which can be applied to the Perempatan Duren. This is because the degree of saturation value obtained is 0.75 for alternative 4 and alternative 5 solutions. The degree of saturation value obtained is in accordance with the requirements of the 2014 PKJI, namely ≤ 0.85. In the calculation for forecasting vehicle volume for the next 5 years, alternative 5 and alternative 5 solutions can be applied to the Perempatan Duren. This is because the value of the degree of saturation for 2023 to 2027 ≤ 0.85 based on the terms of the PKJI 2014.